1989
DOI: 10.1007/bf02943038
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of alprazolam with amitriptyline in the treatment of patients with neurotic or reactive depression

Abstract: 104 patients suffering from neurotic or reactive depression were treated with either alprazolam or amitriptyline in randomised, double-blind fashion. Seventeen patients were either lost to follow-up or withdrawn before week 2 (13 due to side effects and 1 because she was feeling better). A further 7 patients did not comply with the protocol, giving a total of 24 patients whose data were not considered suitable for inclusion in the analysis of therapeutic assessments. Evaluation of the 80 patients (40 in each g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…As for adverse reactions, a significantly greater number of side effects was reported in patients treated with TCA by Singh et al [38], whereas a comparable likelihood of reporting side effects was observed with both BZD and TCA in 3 other studies [35,37,39].…”
Section: Systematic Review Of Rct On the Efficacy Of Bzd In The Treatmentioning
confidence: 83%
See 2 more Smart Citations
“…As for adverse reactions, a significantly greater number of side effects was reported in patients treated with TCA by Singh et al [38], whereas a comparable likelihood of reporting side effects was observed with both BZD and TCA in 3 other studies [35,37,39].…”
Section: Systematic Review Of Rct On the Efficacy Of Bzd In The Treatmentioning
confidence: 83%
“…Participants were assigned at random to the conditions in all studies, and all were double-blind trials. ITT analyses were performed in 8 reports [19,20,23,28,30,31,42,53], completers' data only were reported in 12 studies [25,27,29,37,39,41,44,45,47,49,50,54], and handling of attrition was not reported in 2 studies [46,48].…”
Section: Meta-analysis On the Efficacy Of Bzd In The Treatment Of Depmentioning
confidence: 99%
See 1 more Smart Citation
“…First-line treatments in depression are tricyclic antidepressants (TCAs). Clinical studies in depressed patients showed that alprazolam is at least equally effective as TCAs, such as amitriptyline (13,66,76,126,157,249), imipramine (84,86,87,180,212,277), dosulepine (41), desipramine (85,210), or doxepin (9). However, other studies reported that, although alprazolam provided symptom relief, amitriptyline (124,159,227) and imipramine (103,161) were significantly more effective.…”
Section: Depressionmentioning
confidence: 99%
“…Это доказывалось результатами плацебоконтролируемых исследований [31][32][33]. Одновременно сравнительные двойные слепые исследования продемонстрировали, что алпразолам ослабляет проявления депрессий различной тяжести и генеза почти в той же степени, что и трициклические антидепрессанты [31,[34][35][36] (табл. 2).…”
unclassified